Optimal Placement of Phasor Measurement Units on Shiroro 330kv Grid Network Using Binary Grey Wolf Optimization Algorithm - Kabiru Abubakar Tureta; Sabo Aliyu; Yakubu Abdulrazak (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
Phasor Measurement Units (PMUs) are crucial for improving the control, monitoring, and observability of modern power systems. This research presents an optimal PMU placement strategy for the Shiroro 330 kV grid network using the Binary Grey Wolf Optimization (BGWO) algorithm. The objective is to minimize the number of PMUs required while ensuring full system observability under both normal and contingency conditions. The BGWO algorithm, inspired by the hunting behavior of grey wolves, is a powerful metaheuristic for solving binary optimization problems. Applied to the Shiroro grid, this method demonstrates enhanced observability and systemreliability. Compared to other optimization techniques, BGWO achieves higher accuracy and reduced computational time. The simulation results validate the effectiveness of the proposed approach in achieving cost-effective and reliable PMU deployment for the 330 kV network.